Weight change before and after adenotonsillectomy in children: An analysis based upon pre‐surgery body mass category. (27th May 2020) - Beauchamp, Marshall T.; Regier, Betsy; Nzuki, Anne; Swinburne Romine, Rebecca; Sweeney, Brooke; Liu, Mei; M. Davis, Ann
Abstract: Objectives: To determine the standardised body mass index (BMIz) trajectory before and after adenotonsillectomy/tonsillectomy between children in different weight classifications in a larger sample than has been studied previously, and to identify which patient factors would explain the difference in these outcomes. Design: We used a retrospective chart review and leveraged data of weight status pre‐ and post‐adenotonsillectomy/tonsillectomy from a cohort of paediatric patients seen between May 2004 and April 2017. Setting: Data were collected from an electronic medical record at a single Midwest paediatric health system. Participants: The study population included a convenience sample of 1, 751 paediatric patients who underwent adenotonsillectomy or tonsillectomy and had at least two height and weight measurements recorded on the same date both before and after surgery. Main Outcome Measures: Change in BMIz trajectories before and after surgery. Results: Of 1751 paediatric patients (ages 3‐11) underwent adenotonsillectomy/tonsillectomy procedures. Age at time of surgery and gender were not significant predictors. Children in different weight classifications demonstrated differences in BMIz trajectory after surgery. Children with overweight/obesity experience a decrease in BMIz, whereas children with underweight or normal weight experience an increase in BMIz. Conclusions: Improvement in weight status is seen after surgery: increased BMI for those underweight and decreased BMI for those with overweight/obesity. We advocate for behavioural strategies as a first‐line treatment in children with underweight or overweight/obesity, and results suggest that coordinating these efforts alongside adenotonsillectomy/tonsillectomy when indicated for medical reasons may be warranted. However, further research is needed to confirm these findings due to the observational nature of this study.